Official and Real Biographies in Context of Soviet Tradition of Non-Material Incentives for Labor during Great Patriotic War - N. V. Starikova (Научный диалог, 2021)
The question of the use of the official labor biography in the 30—40s of the twentieth century as a means of instilling a sacred attitude to work in a Soviet person, a method of non-material stimulation of the production process is considered. The relevance of the study is due to the interest in biography in the context of the history of labor, in the authors’ appeal to the problem of forming a new attitude to work during the period of industrialization and the years of the Great Patriotic War. Attention is paid to the role of periodicals. The results of a comparative analysis of the official and real biography, recovered from the materials of the personal file, are presented. The question is raised about the tasks of the official biography of the Hero of Socialist Labor in this period. The novelty of the research is seen in the attraction of unpublished data from the production archive of the Gorky Railway, in the reconstruction of real biographical data. The authors compare the official and real biographies. The possibility of using heroic biography as a method of non-material stimulation of labor has been proved. The author’s reconstruction of the biography of Ivan Georgievich Makarov — Hero of Socialist Labor is presented. The experience of analytical research of documentary historical sources and their comparison with the narrative tradition is described.